Gastroesophageal intussusception secondary to induction of emesis with subsequent development of septic pericardial effusion after corrective surgery. (9th August 2021) - Brincin, C.; Ryan, T.; Harris, K.
Abstract : A juvenile boxer dog was diagnosed with gastroesophageal intussusception that occurred after the induction of emesis with apomorphine. A ventral midline coeliotomy and diaphragmotomy were performed and the intussusception was manually reduced. Despite initial satisfactory recovery, the dog was diagnosed with cardiac tamponade 1 week post‐operatively. Escherichia coli was cultured from pericardial and pleural effusion samples. During subtotal pericardiectomy surgery the pericardium was found to be markedly thickened with adhesions to the epicardium, thoracic wall and diaphragm. Substantial haemorrhage and refractory hypotension necessitated the administration of a blood transfusion during surgery. The dog entered cardiac arrest in the immediate post‐operative period and cardiopulmonary resuscitation was unfortunately unsuccessful. Gastroesophageal intussusception should be considered a possible severe adverse effect of administering apomorhine to induce emesis in dogs. Additionally, septic pericardial and pleural effusions may occur post‐reduction of gastroesophageal intussusception.